A bird’s eye view of my village – Developing participatory geospatial methodology for local level land use planning in the Southern Highlands of Tanzania - Eilola Salla; Käyhkö Niina; Ferdinands Andrew; Fagerholm Nora (Elsevier, 2022)
Despite the large number of participatory mapping and participatory geographical information system (PGIS) applications developed since the 1990s, few studies have utilized participatory mapping in formal planning processes. Evidence is needed regarding their practical applicability in rural land use planning in the Global South and their effectiveness in decision-making in formal planning processes. In this paper, we present participatory mapping and planning methodology that we have co-developed for official village land use planning processes in Tanzania and assess the method’s influence on spatial data quality as well as deliberation and spatial understanding and learning among the participants. We describe 11 literature-based criteria for integrating participatory mapping into spatial planning processes and use them in our assessment. The assessment includes analysis of village land use plan (VLUP) maps and observations as well as interviews and group discussions with participants and facilitators of the planning process. We show that the participatory mapping method with georeferenced images is a powerful tool to capture local spatial knowledge from a wide range of stakeholders and increase the quality of and confidence in spatial planning. As a visual aid, the georeferenced image supports deliberation and detailed examination of the landscape, enhancing spatial understanding and learning about the village landscape. Apart from generating local spatial data, we show that the participatory geospatial method supports the decision-making capacity of participants, which is important for the effectiveness of the method in formal land use planning processes.